Terrestrial hydrometeorology - Shuttleworth, W. James (Wiley-Blackwell, 2012)
"Both hydrologists and meteorologists need to speak a common scientific language, and this has given rise to the new scientific discipline of hydrometeorology, which deals with the transfer of water and energy across the land/atmosphere interface.Terrestrial Hydrometeorology is the first graduate-level text with sufficient breadth and depth to be used in hydrology departments to teach relevant aspects of meteorology, and in meteorological departments to teach relevant aspects of hydrology, and to serve as an introductory text to teach the emerging discipline of hydrometeorology.The book will be essential reading for graduate students studying surface water hydrology, meteorology, and hydrometeorology. It can also be used in advanced undergraduate courses, and will be welcomed by academic and professional hydrologists and meteorologists worldwide"--Provided by publisher.